2019
DOI: 10.1007/s42452-019-0849-x
|View full text |Cite
|
Sign up to set email alerts
|

Drivers and responses to climate variability by agro-pastoralists in Kenya: the case of Laikipia County

Abstract: This paper examines factors influencing the choice of response strategies and the actual strategies smallholder farmers use to respond to the effects of climate variability in transitional climatic zones of Africa, specifically Laikipia West Sub-County in Kenya. Data for this study were collected from 392 randomly selected smallholder farmers, using a structured questionnaire. The study used principal component analysis to group together related strategies that farmers used to respond to the effects of climate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…In Laikipia, perceptions on the access to weather information (e.g., knowing the rainfall patterns expected), increased agricultural information, access to agricultural extension services, credit availability, and higher levels of education enabled farmers to increase the use of hybrid seeds and enhance productivity (Atsiaya et al, 2019). Farmers' expectations of upcoming seasonal weather are important measures of farm decision-making in Laikipia County where Rembold et al (2014) analyzed the impacts of food security and found that KMD forecasts, European Centre for Medium-Range Weather Forecasts (ECMWF) seasonal forecast, and Global Forecasting System can predict varied food situations in the country.…”
Section: Barriers To the Use Uptake And Adoption Of Weather And Climate Information By Farmersmentioning
confidence: 99%
“…In Laikipia, perceptions on the access to weather information (e.g., knowing the rainfall patterns expected), increased agricultural information, access to agricultural extension services, credit availability, and higher levels of education enabled farmers to increase the use of hybrid seeds and enhance productivity (Atsiaya et al, 2019). Farmers' expectations of upcoming seasonal weather are important measures of farm decision-making in Laikipia County where Rembold et al (2014) analyzed the impacts of food security and found that KMD forecasts, European Centre for Medium-Range Weather Forecasts (ECMWF) seasonal forecast, and Global Forecasting System can predict varied food situations in the country.…”
Section: Barriers To the Use Uptake And Adoption Of Weather And Climate Information By Farmersmentioning
confidence: 99%
“…In two studies conducted separately in Kenya, most of the measures applied an adaptation strategy for climate change are found statistically significant (Kinuthia et. al., 2018;Atsiaya et. al., 2019).…”
Section: The Factors Affecting Adaptation To Climate Changementioning
confidence: 99%
“…al., 2016, Zizinga et. al., 2017, Fadina and Barjolle, 2018, Atsiaya et. al., 2019, Kinuthia et.…”
Section: Introductionmentioning
confidence: 99%
“…Planned adaptation strategies should thus ensure that the underlying determinants of adoption, such as access to knowledge and information, exist alongside other relevant enabling factors, including endowment with productive assets, human capital (education and skills), and institutional support (e.g., farmer groups and collective action; Atsiaya et al, 2019;Bedeke et al, 2019). Profiling different vulnerability categories is also extremely important because smallholders adopt different strategies according to their degree of sensitivity and adaptive capacity beyond their actual exposure to climate change.…”
Section: Key Messages Emerging From the Evidence Synthesis Scaling Up...mentioning
confidence: 99%